Productivity Improvement Training: Capacity Building For Human Resource Managers In Deli Serdang Regency, Sumatera Utara - Halim, Hendra; Teuku Meldi Kesuma; M. Ridha Siregar; Teuku Muhammad Syahrizal; Khairil Umuri; Dinaroe; Iskandarsyah; Fakhrurrazi; Hamdi Harmen; Ahmad Nizam; Farid (Universitas Muhammadiyah Malang, 2023)
Purpose – The purpose of this community service initiative is to provide comprehensive productivity enhancement training specifically tailored for HR managers working in various companies. This training aims to equip them with the knowledge and skills necessary to improve productivity within their respective organizations. Design/methodology/approach – The training program utilizes a multifaceted approach, combining traditional lecture-based teaching, case method studies, and project-based learning. It spans over a 5-day period and took place at the Balai Besar Pelatihan Vokasi dan Produktivitas (BBPVP) Medan in August 2022. The training encompasses various modules, including an introductory session on productivity, planning, organizational strategies, and methods for analyzing and enhancing productivity. To assess the effectiveness of the training, participants undergo pre-test and post-test evaluations to measure the extent of their knowledge enhancement. Findings – The evaluation results reveal a noteworthy improvement in participants' comprehension and proficiency in enhancing productivity within their workplace environments. This indicates that the diverse and interactive training methods employed in the program directly contribute to enhancing productivity-related skills among HR managers. Originality/value – This community service initiative holds significant value as it addresses a specific and critical need for HR managers in various companies. By offering specialized training in productivity enhancement, it equips participants with valuable skills that can positively impact their organizations. Additionally, the use of diverse training methods ensures engagement and effective learning. Despite time constraints and potential challenges, this initiative has the potential to drive meaningful change and serve as a model for future community-focused training programs.